Extraction of Air Gun Pellet in Lung Base Thoracic Vertebrae Region with Lateral Extracavitary Approach: A Case Report - Adji, Novan Krisno; Putri, Komang Yunita Wiryaning; Indreswari, Laksmi; Nugraha, Muhammad Yuda; Habibi, Ali (Faculty of Medicine, University of Jember, 2023)
Thoracic gunshot injuries are associated with significant morbidity and mortality, but fatal accidents from air guns are rare. Surgery in this area is challenging, especially if the gun pellet penetrates the visceral organ like the lung. In this case, we present a case of an 18-year-old male who came to the emergency department with an air gunshot (pellet) that penetrated the chest and settled in the lung base. After being shot by an air gun, the patient came with pain in the right back and weakness in both lower extremities. Based on the radiological examination, metallic corpus allienum measuring ± 0.8 x 0.7 cm has shown at the lung base as high as the Thoracic 12 vertebrae, 9.5 cm right lung laceration, right hemothorax, and emphysema subcutis on the right inferior side of hemithorax. The patient planned surgery to extract the corpus allienum through a lateral extra cavitary approach to expose the lungs at the level of the Th10-12 vertebrae. The lateral extra cavitary approach can be an alternative, less invasive method to extract foreign body lung base in front of vertebrae thoracic region.